PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA KARYAWAN (STUDI PADA PT PLN (PERSERO) WILAYAH IX MALUKU DAN MALUKU UTARA) - Kowey, Wylda Olivia (Arthavidya Jurnal Ilmiah Ekonomi, 2015)
This study aims to analyzethe style of leadership that consists ofinstruction style, style consultation, participation style, and the style of thedelegation and its influence on employee motivation of PT PLN (Persero)Region IX Malukuand North Maluku. Data were collected using aquestionnaire distributed to 52 employees were taken randomly asrespondents. The data collected were analyzed using multiple regressionAnalsisi with SPSS19. The results showed that the leadership style of managersconsisting leadership style instruction, consultation, participation, anddelegates significant effect in increasing employee motivation PT. PLN(Persero) Malukuand North Maluku Region. While the participation ofleadership styleis the most dominant style of leadership in improving employeemotivation PT. PLN (Persero) Region Maluku and North Maluku.Keywords : leadership style, the style of instruction, style consultation,participation style, the style of delegation, motivation